A Meta-analysis of the effect of five-element music therapy for patients with insomnia (五行音乐对失眠患者干预效果的Meta分析) - WU Yang (吴洋); GAI Haiyun (盖海云); MA Minghui (马明会) (中西医结合护理)
Objective To evaluate the effect of five-element music therapy for patients with insomnia based on the results of Meta-analysis. Methods By searching Chinese databases such as CNKI, Wanfang Data and VIP, randomized controlled trials of five-element music therapy in treating insomnia were collected, and retrieval time-limit was from the establishment of the database to April 2022. Meta-analysis was performed on the papers that met the nadir criteria. Results Twelve studies with a total of 1346 cases were finally included. The results showed that the efficiency of five-element music therapy was better than conventional treatment ［OR=2. 54, 95% CI (1. 76, 3. 68); Z=4. 95, P<0. 00001］ and the recovery rate of five-element music therapy was better than conventional treatment ［OR=2. 54, 95% CI (1. 76, 3. 68); Z= 4. 95, P<0. 00001］, and sleep quality was better with five-element music therapy than conventional treatment ［MD=-1. 69; 95% CI (-2. 48, -0. 91); Z=4. 21, P<0. 00001］. There was no significant difference between five-element music therapy and conventional treatment in prolonging patients' sleep time and TCM integral score. Conclusion five-element music therapy was superior to conventional treatment in terms of clinical efficacy in treating patients with insomnia and could improve patients' sleep quality, but its efficacy in prolonging patients' sleep time and TCM evidence points was not significant, which may be related to the insufficient literature. (目的 基于Meta分析结果评价五行音乐治疗失眠患者的有效性。方法 通过检索中国知网、万方、维普等中文数据库, 收集自建库起至2022年4月五行音乐治疗失眠患者的随机对照试验, 对符合纳入标准的文献进行Meta分析。结果 最终纳入12篇文献, 共纳入1346例; 结果显示, 五行音乐的有效率优于常规治疗［OR=2. 54, 95%CI(1. 76, 3. 68); Z=4. 95, P＜0. 00001］, 五行音乐的痊愈率优于常规治疗［OR=2. 54, 95%CI(1. 76, 3. 68); Z=4. 95, P＜0. 00001］, 五行音乐的睡眠质量优于常规治疗［MD=-1. 69; 95%CI(-2. 48, -0. 91); Z=4. 21, P＜0. 00001］, 但五行音乐在延长患者睡眠时间、中医证候积分方面, 与常规治疗相比, 差异没有统计学意义。结论 五行音乐在治疗失眠患者的临床疗效上优于常规治疗, 可以改善患者的睡眠质量, 但在延长患者睡眠时间、中医证候积分方面疗效不显著, 可能与纳入文献较少有关, 需要更多有质量的文献支持。)